2021
DOI: 10.1002/pc.25986
|View full text |Cite
|
Sign up to set email alerts
|

Effect of silica nanoparticles on physical, mechanical, and wear properties of natural fiber reinforced polymer composites

Abstract: Hemp-sisal natural fiber-reinforced hybrid epoxy composites containing a varying proportion of silica nanoparticles (0, 1, 2, 3, and 4 wt%) were manufactured and subsequently evaluated for physical, mechanical, and sliding wear properties. The density of the composite was found to increase, whereas void content was found to decrease with the increase of silica nanoparticles content. The composites containing 2 wt% silica nanoparticles exhibit maximum tensile strength, impact strength, and hardness, whereas the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 46 publications
2
31
0
Order By: Relevance
“…Figure 13 displays the SEM images F I G U R E 1 2 Mode and extent of damage under 50 J impact energy of various specimens with different magnifications. As mentioned earlier, the failure mechanisms in the composite sandwich panels including fiber breakage, fiber buckling, [15] matrix cracking, core crushing and delamination were confirmable by SEM images as well.…”
Section: Analysis Of Damaged Zone Morphology By Semsupporting
confidence: 73%
See 1 more Smart Citation
“…Figure 13 displays the SEM images F I G U R E 1 2 Mode and extent of damage under 50 J impact energy of various specimens with different magnifications. As mentioned earlier, the failure mechanisms in the composite sandwich panels including fiber breakage, fiber buckling, [15] matrix cracking, core crushing and delamination were confirmable by SEM images as well.…”
Section: Analysis Of Damaged Zone Morphology By Semsupporting
confidence: 73%
“…Hence, the presence of 2 wt% nanosilica in the matrix practically enhanced the impact resistance. Singh and et al [ 15 ] demonstrated that incorporating 3 wt% silica nanoparticles into the fiber‐reinforced hybrid epoxy composites improved the flexural strength.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the three parameters (load = 30 N, speed = 100 rpm, sliding distance = 50 m) represented an ideal combination for potential use of jute-coir composites with eggshell powder and nanoclay fillers for use in automotive components that required relative motion, such as brushes, washers, and spacers. In this case, the ceramic fillers may compete with a hardening function typically played in natural fiber composites for wear-resistant structures by the introduction of silica [39]. In general terms, introduction of natural fibers, such as, e.g., kenaf [40], jute [41], or coir [42], does improve the wear characteristics of unsaturated polyester resins.…”
Section: Discussionmentioning
confidence: 99%
“…The 'smaller is better' characteristics is used to represent the S/N ratio for minimum slurry erosion rate as shown in Equation ( 14). [37][38][39][40][41] S=N ¼ À10Log…”
Section: Experimental Designmentioning
confidence: 99%